Hospitality in hospitals: The importance of caring about the patient. Issue 2 (1st June 2016) - Kelly, Rosalind; Losekoot, Erwin; Wright-StClair, Valerie A.
Evidence suggests that hospital patients receive the medical treatment they need but are sometimes left feeling depersonalized and alienated with their overall treatment. This New Zealand study explored the lived experience of hospitality among adults during their recent hospital stay. A hermeneutic phenomenological methodology was used to design and conduct the study. Seven participants, aged 22 to 65 years, who had spent at least three days in a hospital for elective surgery were purposively recruited. Data were gathered using semi-structured, conversational-style individual interviews. Participant-validated, coherent stories were drawn from the transcripts and analysed. The findings revealed that hospitality showed itself in different ways to the participants. When present, they experienced feelings of comfort, of being at ease and of being healed. The implications for health care practitioners are that offering often small, yet heartfelt acts of hospitality may evoke powerful lived experiences that benefit the patient, suggesting that caring about the patient is an important element of the healing process.